Interleukin-dependent modulation of the expression of MHC class I and MHC class II genes in chicken HD11 cells. (September 2020) - Truong, Anh Duc; Hong, Yeojin; Ly, Viet Duc; Nguyen, Huyen Thi; Nguyen, Chinh Thi; Vu, Hao Thi; Chu, Nhu Thi; Van Hoang, Tuan; Thanh Tran, Ha Thi; Dang, Hoang Vu; Hong, Yeong Ho
Abstract: Interleukins (ILs) regulate cell surface antigens known as activation markers, which have distinct functional roles. However, the regulation of major histocompatibility complex (MHC) class I, MHC class II, and related genes by cytokines in chickens is not well understood. In the present study, we evaluated the influence of certain recently discovered chicken interleukins—i.e., IL-11, IL-12B, IL-17A, IL-17B, IL-26, and IL-34—on the expression and regulation of genes related to MHC class I, MHC class II, and the associated proteins in an HD11 chicken macrophage cell line. We used quantitative reverse transcription polymerase chain reaction (qRT-PCR), immunocytochemical, and flow cytometric analyses to assess dose- and time-dependent expression in the HD11 cell line and found that the ILs induced MHC class I, MHC class II, and associated protein. As NF-κB is actively involved in cell activation and is constitutively activated in many immune cells, we also determined whether NF-κB regulates MHC class I, MHC class II, and related gene expression in the HD11 cell line. The NF-κB inhibitor sulfasalazine (Sz) dose-dependently inhibited MHC class I and MHC class II in the HD11 cell line. Sz also downregulated the expression of MHC class I, MHC class II, and the associated proteins in the IL-induced HD11 cell line. The expression of MHC class I, MHC class II, and associated genes was accompanied by the Sz-sensitive degradation of the p65 (RelA) and p50 subunits of NF-κB and IκBα. Our results indicate that the different effects of each IL on the expression of genes related to MHC class I, MHC class II, and the associated proteins are involved with the regulation of the dose and duration of antigenic peptide presentation and, thus, also influence Th1, Th2, and Th17 production. Highlights: Chicken interleukins recombinant proteins were induced MHC class I, MHC class II, and related genes in HD11 cell line. NF-κB regulates MHC class I, MHC class II, and related gene expression in the HD11 cell line. NF-κB inhibitor sulfasalazine inhibited MHC class I and MHC class II in HD11 cell line. The activation of sulfasalazine through by p65 (RelA) and p50 subunits of NF-κB and IκBα.